THE EFFECT OF SERVICE EXELLENCE AND PRICE ON CUSTTOMER LOYALTY AT VILLA AIR BALI BOUTIQUE RESORT AND SPA - Anak Agung Sasmita Dewi; I Ketut Astawa; Budi Susanto (Politeknik Negeri Bali, 2018)
This research is motivated by the writer's curiosity towards customer response of Villa Air Bali Boutique Resort and Spa in terms of customer loyalty. This is because Villa Air Bali Boutique Resort and Spa has customers who are loyal to the services provided although in Bali, especially Seminyak area there are also many resort villas that offer good service at a cheaper price. The purpose of this study was to determine the effect of excellence service and price on customer loyalty. Sampling technique using non probability sampling with purposive sampling type. Respondents in this study up to 100 respondents. The analysis used in this research is quantitative analysis using SPSS software version 17.0 for Windows, where previously tested the validity, reliability, multiple regression analysis, t test, F test, coefficient of determination and multiple correlation analysis first. The results of this study indicate that the excellence service (X1) and price (X2) partially or simultaneously affect customer loyalty (Y).